Study On The Implementation Of The Social Rehabilitation Program Policy For Physical Disabilities At East Java Provincial Social Service. - Ainun Jariyah; Ulul Albab; Priyanto Priyanto; Abeda Muhammad Iqbal (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the implementation of social rehabilitation program policies for people with physical disabilities at the Technical Implementation Unit (UPT) Social Rehabilitation Bina Laras Pasuruan under the East Java Provincial Social Service. Using George C. Edwards III's policy implementation model, this research analyses four key variables: communication, resources, disposition, and bureaucratic structure. This qualitative descriptive study employed interviews, observation, and documentation as data collection techniques. The findings reveal that the implementation has been running reasonably well, with clear communication channels established between program implementers and beneficiaries. However, several challenges persist, including limited human resources, particularly professional social workers and medical rehabilitation specialists, as well as budget constraints affecting service quality. The disposition of implementers shows a positive attitude toward policy goals, though the bureaucratic structure requires improvement in coordination mechanisms. The study concludes that while the social rehabilitation program has improved the quality of life for persons with disabilities, optimising policy implementation requires addressing resource limitations, strengthening inter-agency coordination, and enhancing community participation in rehabilitation efforts